On the natural history of emotions: Darwin’s legacy - Jesus, Paulo Renato (2014)
One of the most striking applications of Darwinian principles resides in the evolutionary account of expression of emotions. The main purpose of this paper is to ask some fundamental questions concerning this realm of Darwinian investigations and its implicit or explicit legacy in contemporary psychology of emotions, which appears inhabited by the essential tension between the primacy of embodiment (from James to Damasio) and that of cognitive mediation (from Peirce to Lazarus). One should ask again: what is an emotion? Is it reducible to a bodily expression or is there any qualitative difference between emotion and expression? Why do emotions belong to the phenomena of life? How do the grammar of life and the grammar of culture interact in emotional expressions? What is the ―truth‖ of Darwin’s principles on expressions and what degree of coherence can be detected when one attempts at integrating the theory of emotions in the larger picture of the evolution of life forms and cultural meaningful phenomena? Darwin is systematically attracted towards normative invariants, that is, nomological relationships and functions which organise a dynamic morphogenetic process. Thus, Darwin’s theory of expression of emotions identifies a set of three universal principles that complement each other. These comprise not only the notion of adaptive behaviour, association of learned habits and evolution of instinct, but also that of body structure (specially the web of muscles that define and constrain the landscape of the face), inheritance of movements and independent action of the nervous system. Darwin develops a fine dynamic bio-semiology: he sheds light on a presupposed unconscious universal grammar of emotional expression, communication and comprehension, where profitability and uselessness intertwine. This general bio- semiotics invites a special bio-logic that gives room for epigenetic landscapes, and thus to individual creativity and idiosyncrasy: the art of being in my body as on stage.